TLR9-Targeted STAT3 Silencing Abrogates Immunosuppressive Activity of Myeloid-Derived Suppressor Cells from Prostate Cancer Patients - Hossain, Dewan M. S.; Pal, Sumanta K.; Moreira, Dayson; Duttagupta, Priyanka; Zhang, Qifang; Won, Haejung; Jones, Jeremy; D'Apuzzo, Massimo; Forman, Stephen; Kortylewski, Marcin (Clinical cancer research, 2015)
Purpose: Recent advances in immunotherapy of advanced human cancers underscored the need to address and eliminate tumor immune evasion. The myeloid-derived suppressor cells (MDSC) are important inhibitors of T-cell responses in solid tumors, such as prostate cancers. However, targeting MDSCs proved challenging due to their phenotypic heterogeneity. Experimental Design: Myeloid cell populations were evaluated using flow cytometry on blood samples, functional assays, and immunohistochemical/immunofluorescent stainings on specimens from healthy subjects, localized and metastatic castration-resistant prostate cancer patients. Results: Here, we identify a population of Lin−CD15HICD33LO granulocytic MDSCs that accumulate in patients' circulation during prostate cancer progression from localized to metastatic disease. The prostate cancer–associated MDSCs potently inhibit autologous CD8+ T cells' proliferation and production of IFNγ and granzyme-B. The circulating MDSCs have high levels of activated STAT3, which is a central immune checkpoint regulator. The granulocytic pSTAT3+ cells are also detectable in patients' prostate tissues. We previously generated an original strategy to silence genes specifically in Toll-like Receptor-9 (TLR9) positive myeloid cells using CpG-siRNA conjugates. We demonstrate that human granulocytic MDSCs express TLR9 and rapidly internalize naked CpG-STAT3siRNA, thereby silencing STAT3 expression. STAT3 blocking abrogates immunosuppressive effects of patients-derived MDSCs on effector CD8+ T cells. These effects depended on reduced expression and enzymatic activity of Arginase-1, a downstream STAT3 target gene and a potent T-cell inhibitor. Conclusions: Overall, we demonstrate the accumulation of granulocytic MDSCs with prostate cancer progression and the feasibility of using TLR9-targeted STAT3siRNA delivery strategy to alleviate MDSC-mediated immunosuppression. Clin Cancer Res; 21(16); 3771–82. ©2015 AACR.